Genome‐wide identification and comparison of mRNAs, lncRNAs and circRNAs in porcine intramuscular, subcutaneous, retroperitoneal and mesenteric adipose tissues. (14th April 2019) - Liu, X.; Wei, S.; Deng, S.; Li, D.; Liu, K.; Shan, B.; Shao, Y.; Wei, W.; Chen, J.; Zhang, L.
Summary: Many types of RNAs, including messenger RNAs (mRNAs), long noncoding RNAs (lncRNAs) and circular RNAs (circRNAs), play crucial roles in regulating fat cell differentiation and tissue development. However, the expression profiles of these RNAs in different adipose tissues are still largely unknown. To shed light on this issue, we performed a transcriptome analysis of mRNAs, lncRNAs and circRNAs obtained from intramuscular adipose tissue, subcutaneous adipose tissue, retroperitoneal adipose tissue and mesenteric adipose tissue of Chinese Erhualian pigs. A number of differentially expressed mRNAs, lncRNAs and circRNAs were identified among the four adipose tissues. Tissue‐specific analysis indicated that circRNAs exhibited the highest tissue specificity among mRNAs, lncRNAs and circRNAs, whereas intramuscular adipose tissue had the most tissue‐specific genes among the four adipose tissues. Gene Ontology analysis showed that differentially expressed mRNAs among groups were involved mainly in lipid metabolism and immune inflammatory response processes. Furthermore, the co‐expression network construction of mRNAs–lncRNAs revealed that several important lncRNAs, such as MSTRG.426159 and MSTRG.604206, might associate with lipid metabolic process. Taken together, these data provide a genome‐wide resource of mRNAs, lncRNAs and circRNAs potentially involved in porcine fat metabolism, thus improving understanding of their function in diverse adipose tissues.